Evaluation on different UAV’s georeferencing points to generate accurate orthophoto and digital terrain model / Muhammad Hafiz Aizuddin Mohd Zaidi and Khairul Nizam Tahar - Mohd Zaidi, Muhammad Hafiz Aizuddin; Tahar, Khairul Nizam (UiTM Press, 2021)
UAV or drone application of autonomy ranging can be divided into several levels, from basic hovering and position over trajectory tracking and waypoint navigation to fully autonomous navigation. This study used the DroneDeploy application for an autonomous flight mission. It is the process of taking photographs from an aircraft or other flying objects with a camera mounted on them to produce a three-dimensional (3D) map from the images captured, including a digital terrain model (DTM) and orthophotos. As for this study, the same output will be generated, but different flight parameter applications were used. Therefore, the study determined the optimum number of ground control points (GCPs) and evaluated the accuracy of the final results for each flight design. Acquired data were processed using the Pix4D modeller software due to the user-friendly factor and faster processing rate offered by the software. The results were analysed, and recommendations were made for future study improvement and to avoid similar problems. This study is useful for the mapping industry to achieve high accuracy results.